An appetite to win: Disordered eating behaviours amongst competitive cyclists - Roberts, C. J.; Hurst, H. T.; Keay, N.; Hamer, J.; Sims, S.; Schofield, K. L.; Hardwicke, J. (2024)
Competitive cyclists may be vulnerable to disordered eating (DE) and eating disorders (ED) due to perceived body composition optimization and external influences within cycling culture and from stakeholders. Therefore, this study aimed to assess DE and ED risk in competitive cyclists using the Eating Attitudes Test (EAT-26), explore differences in responses based on sex, discipline, and level of competition, and to gain insights into contributing factors towards DE via open-ended survey questions. In total, 203 participants completed a mixed-method questionnaire. Eating disorders were reported by 5.7% (n = 11) of participants, with three being historic cases. The median (inter-quartile range) EAT-26 score was 8 (12) of a total possible score of 78. Disordered eating risk was observed in 16.7% of participants due to an EAT-26 score =20. Female participants had significantly higher scores than male participants (12.5 ± 17.5 vs. 6.5 ± 10.0; p = 0.004). There was no significant difference between road cyclists and off-road cyclists (7.0 ± 13.25 vs. 8.0 ± 10.5; p = 0.683).